The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.2147/prom.s243867
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antiepileptic Drug Treatment Outcomes and Seizure-Related Injuries Among Adult Patients with Epilepsy in a Tertiary Care Hospital in Ethiopia</p>

Abstract: Objective: Anti-epileptic drugs (AEDs) are the primary therapeutic modalities for epilepsy management. However, one-third of epileptic patients continue to experience seizure even with appropriate AED use. Patients with epilepsy are at increased risk for seizure-related injury and they have higher incidences of home, street and work accidents. There is a paucity of data on AED use pattern and treatment outcomes among patients with epilepsy in the tertiary hospitals of Ethiopia. Therefore, the aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 25 publications
(34 reference statements)
2
33
2
Order By: Relevance
“…e probable explanation might be due to the difference in study design (retrospective cohort study design was used in USA), but the current study employed the crosssectional study design and newer AEMs (gabapentin, lamotrigine, levetiracetam, and topiramate) which were commonly used in USA and France [10,31,32]; since newer medications have a lower side effect, the adherence rate could be higher. In Ethiopia, cheap and old generation antiepileptic drugs like phenobarbitone are highly used, and these might increase the nonadherence rate [33].…”
Section: Discussionmentioning
confidence: 99%
“…e probable explanation might be due to the difference in study design (retrospective cohort study design was used in USA), but the current study employed the crosssectional study design and newer AEMs (gabapentin, lamotrigine, levetiracetam, and topiramate) which were commonly used in USA and France [10,31,32]; since newer medications have a lower side effect, the adherence rate could be higher. In Ethiopia, cheap and old generation antiepileptic drugs like phenobarbitone are highly used, and these might increase the nonadherence rate [33].…”
Section: Discussionmentioning
confidence: 99%
“…Many guidelines now recommend the use of monotherapy with AED for most patients because of similar efficacy and better tolerability compared to polytherapy [ 11 ]. As reported in some prior studies, the proportion of monotherapy is pretty high and can be up to 71% [ 12 , 13 ]. This study’s result also showed a preference for monotherapy in over 70% of the patients.…”
Section: Discussionmentioning
confidence: 90%
“…Twentythree primary studies were included in the present systematic review and meta-analysis. These studies were conducted in different parts of Ethiopia (from Amhara seven primary articles [7,[13][14][15][16][17][18], Oromiya eight [8,9,[19][20][21][22][23][24], Addis Ababa four [25][26][27][28], Tigray two [9,29], and Southern Nation, Nationalities, and People two articles) [30,31]. The sample size of the included primary studies was considerably variable ranging from 121 to 415 participants.…”
Section: 2mentioning
confidence: 99%
“…Regarding the seizurefree period, two studies assessed seizure freedom over one month [6,21], one study over two months [17], two studies over three months [7,14,25], and the remaining studies assessed seizure freedom over at least six months. Concerning the age groups, one study included only pediatric patients [7], two studies included all age group patients [13,19], and the remaining studies included only adult patients [6,8,9,[14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31]. Regarding the antiepileptic drugs, most of the patients were treated with monotherapy and the commonly used drugs were phenobarbitone, phenytoin, carbamazepine, and valproic acid [6-8, 17, 20, 26].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation